Restoring and resuscitating the cultural landscape of Kg Pulau Ketam, Perlis / Mohammad Azam Fikri, Faridatul Akma Abd Latif and Salina Mohamed Ali - Fikri, Mohammad Azam; Abd Latif, Faridatul Akma; Mohamed Ali, Salina (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
This paper will discuss the final comprehensive design restoring and resuscitating the cultural of landscape of Kampung “Pulau Ketam’. The village faces annual flood events leading to degradation of existing significant properties as well as developments that demolish the genus loci of the site as a cultural fisherman village. As to encounter these issues, the aims of this article to restore and resuscitate the cultural landscape of Kampung “Pulau Ketam” with enhance the traditional fisherman Malay village livelihood by using eco-efficient and ecological treatment. The projects covering an area of 821 km2, Perlis is the smallest state in Malaysia. It is located at the northern part of the west coast of Peninsular Malaysia (6030’N and 100o15’E). In 2010, the total population was recorded at 245,636 persons with a density of 276.5/km2. The state economy is dominated by agriculture accounting for 80.5% of land use in the state with the dominant crops being rice, sugar, herbs, rubber and fruits. Forestry and fishery are also important economic sectors. The capital city of Perlis is Kangar which all case studies are in this district. The research highlighted the significant of the site study divided into three phases of sustainable interventions; 1) conservation of natural landscape 2) ecological conservation and preservation 3) resilience through protection of natural landscape, adaptive design on flooding, cultural landscape design interpretation and multiple land uses in fisherman village design program as to sustain the cultural landscape by integrating it with sustainable practice.